2022
DOI: 10.3390/biology11081247
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable and O2-Insensitive Pyruvate Decarboxylases from Thermoacidophilic Archaea Catalyzing the Production of Acetaldehyde

Abstract: Pyruvate decarboxylase (PDC) is a key enzyme involved in ethanol fermentation, and it catalyzes the decarboxylation of pyruvate to acetaldehyde and CO2. Bifunctional PORs/PDCs that also have additional pyruvate:ferredoxin oxidoreductase (POR) activity are found in hyperthermophiles, and they are mostly oxygen-sensitive and CoA-dependent. Thermostable and oxygen-stable PDC activity is highly desirable for biotechnological applications. The enzymes from the thermoacidophiles Saccharolobus (formerly Sulfolobus) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…venenatum, which results in the loss of carbon sources, is one of the dominant factors limiting the efficient conversion of glucose. In filamentous fungi, pyruvate decarboxylase, catalyzing the conversion of pyruvate to CO 2 and acetaldehyde, is located upstream of the ethanol synthesis pathway. , Therefore, mining and deleting the major pyruvate decarboxylase gene are expected to improve the carbon conversion ratio of mycoprotein synthesis in F. venenatum by eliminating the byproduct ethanol synthesis and reducing CO 2 emissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…venenatum, which results in the loss of carbon sources, is one of the dominant factors limiting the efficient conversion of glucose. In filamentous fungi, pyruvate decarboxylase, catalyzing the conversion of pyruvate to CO 2 and acetaldehyde, is located upstream of the ethanol synthesis pathway. , Therefore, mining and deleting the major pyruvate decarboxylase gene are expected to improve the carbon conversion ratio of mycoprotein synthesis in F. venenatum by eliminating the byproduct ethanol synthesis and reducing CO 2 emissions.…”
Section: Resultsmentioning
confidence: 99%
“…In filamentous fungi, pyruvate decarboxylase, catalyzing the conversion of pyruvate to CO 2 and acetaldehyde, is located upstream of the ethanol synthesis pathway. 26,42 Therefore, mining and deleting the major pyruvate decarboxylase gene are expected to improve the carbon conversion ratio of mycoprotein synthesis in F. venenatum by eliminating the byproduct ethanol synthesis and reducing CO 2 emissions. A genome-wide search revealed that six putative pyruvate decarboxylase genes, namely, FvPDC1 (FVRRES_04483), FvPDC2 (FVRRES_05923), FvPDC3 (FVRRES_07836), FvPDC4 (FVRRES_10917), FvPDC5 (FVRRES_12505), and FvPDC6 (FVRRES_12865), were identified in F. venenatum.…”
Section: Mining Of the Major Pyruvate Decarboxylasementioning
confidence: 99%